Analysis of the Relationship Between Environmental Health Factors and Stunting Incidence in Indonesia - Yossi Ismardiani; Fahmi Ichwansyah; Aripin Ahmad; Asnawi Abdullah; Radhiah Zakaria (Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia ranks fifth globally in stunting prevalence, with approximately 30.8% or 23 million children affected. Stunting can impair physical growth, brain development, metabolism, and intelligence, thereby reducing the quality of Indonesia’s human resources. One of the key contributing factors is poor nutrition, which is closely linked to inadequate access to safe drinking water and poor sanitation. This study aimed to analyze the relationship between environmental health factors and stunting in Indonesia using secondary data from the Indonesian Health Profile (2015–2020), covering all 34 provinces. The research applied a descriptive-analytic approach with a cross-sectional design and quantitative analysis using linear regression. The analysis included three models: (1) unadjusted, (2) adjusted for year and province, and (3) adjusted for year, province, poverty, and HDI. The findings showed that the national stunting rate declined from 22.76% in 2015 to 12.70% in 2020, with East Nusa Tenggara (NTT) consistently reporting the highest rates. Bivariate analysis revealed that access to safe drinking water, proper sanitation, community-based sanitation (STBM), TPM compliance, poverty, adequate housing, and HDI were significantly associated with stunting (p < 0.05). After adjusting for confounders, the most influential variables were access to safe drinking water, TPM compliance, and adequate housing. Among these, access to safe drinking water explained the highest variation in stunting rates (21.08%). These results suggest that environmental health—particularly clean water access, food hygiene, and proper housing—plays a crucial role in addressing stunting. Therefore, strengthening basic infrastructure and promoting clean and healthy living behavior (PHBS) are essential for stunting prevention in Indonesia.Keywords: Stunting, Safe Drinking Water, Sanitation, Environmental Health, Linear Regression.